Differential expression of progesterone receptor isoforms related to PGR +331g/a polymorphism in endometriosis: A case-control study - Sepideh Mousazadeh; Azadeh Ghaheri; Maryam Shahhoseini; Reza Aflatoonian; Parvaneh Afsharian (Shahid Sadoughi University of Medical Sciences, 2019)
Background Endometriosis are defined as a progesterone-resistance disease. Two progesterone receptor (PR) isoforms, namely PR-A and PR-B, mediate the special effects of progesterone. One of the most effective polymorphism in the promoter region of PGR is the +331G/A. Objective The differential expression level of PR isoforms due to +331G/A polymorphism may be able to influence the function of progesterone and reduce the susceptibility of endometriosis. Materials and Methods This analytic, case-control study was carried out at Royan Institute, Tehran, Iran. Whole-blood samples were collected from 98 infertile women undergoing laparoscopy for endometriosis and 102 healthy fertile women. After DNA extraction, genotype frequencies were determined by polymerase chain reaction-restriction fragment length polymorphism. Then, RNA was extracted from the selected eutopic tissue samples of endometriosis patients. Analysis of PR-A and PR-B mRNA expressions were performed using Real-time polymerase chain reaction. Results The frequency distribution of GG, GA genotypes in +331G/A polymorphism was 98.04%, 1.96% in the patients and 97.96%, 2.04% in the control groups, respectively (p = 0.968). Although our data did not show any significant association with +331G/A in the patient and control groups, we were able to demonstrate significantly higher expression level of PR-B and no significant lower expression level of PR-A isoforms in patients by favoring GA to GG genotypes (p = 0.017, p = 0.731, respectively). Conclusion Our findings show that patients with GA genotypes had a higher expression level of PR-B compared to patients with GG genotypes.